Implementasi Permen KP Nomor 7 Tahun 2024 tentang Pengelolaan Lobster, Kepiting, dan Rajungan di Kalimantan Timur : Analisis Berdasarkan Data Kuisioner - Fitri Noerhidayanti; Fatmy Yaumil Akhir Jafar; Fitriyana Fitriyana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the implementation of the Minister of Marine Affairs and Fisheries Regulation Number 7 of 2024 concerning the Management of Lobster, Crab, and Blue Swimming Crab in East Kalimantan. As a strategic policy, the regulation aims to ensure sustainable fisheries management through provisions on minimum catch sizes, restocking mechanisms, traceability systems, and law enforcement against illegal fishing and trade. Using an empirical juridical approach, this research collected primary data through questionnaires distributed to fisheries officers, coastal communities, fishers, and aquaculture business actors in East Kalimantan. The results show that the implementation of Regulation No. 7/2024 is generally categorized as moderately effective, with an average Likert score indicating limited but positive compliance. Respondents acknowledged the importance of sustainability principles embedded in the regulation; however, significant challenges persist, including insufficient formal socialization, weak field monitoring, lack of supporting facilities, and inconsistent coordination among implementing agencies (BARANTIN, PSDKP, and local fisheries officers). Qualitative responses highlight that many stakeholders still lack understanding of technical provisions such as minimum size requirements and restocking obligations. The study concludes that while the regulatory framework is normatively comprehensive and aligned with sustainable fisheries principles, its practical effectiveness remains constrained by institutional and socio-cultural factors. Strengthening community engagement, increasing inter-agency coordination, and enhancing enforcement capacity are crucial to optimizing the policy’s impact on the sustainable management of lobster, crab, and blue swimming crab resources in East Kalimantan.